Understanding classroom participation and identity construction of Indonesian EFL teachers as language teaching assistants in U.S. universities - Faridatul Istighfaroh; Ana Kumalasari; Vita Nugrah Septiana; M. Faruq Ubaidillah; Mutmainnah Mustofa (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Studies on the interplay of teacher identity and classroom participation have contributed significant findings in transnational settings. However, in-depth research on identity construction and classroom participation of Indonesian EFL teachers serving as Indonesian language teaching assistants in U.S. universities remains scant. This study aims to explore the identity construction of Indonesian EFL teachers as they enact their roles as Indonesian language teaching assistants in U.S. universities. The study employed a narrative inquiry, collecting data through semi-structured interviews. Three EFL teachers serving as Indonesian language teaching assistants with Fulbright scholarships for Foreign Language Teaching Assistants (FLTA) participated in this study. Findings reveal that participants were actively engaged in all phases of instruction, including pre-teaching preparation, classroom interaction, and post-teaching reflection. Their collaboration with American supervisors and use of various digital tools demonstrates professional adaptability and commitment to effective language teaching. Additionally, participants constructed and negotiated their identities through daily interactions with students, colleagues, and members of the local community. Language use, cultural participation, and religious/national identity served as key dimensions in this identity construction. While participants maintained their Indonesian and Muslim values, they also embraced certain American cultural norms, illustrating the dynamic interplay between cultural adaptation and identity preservation.